(untitled) (Indian Journal of Arid Horticulture, 2013)
A field investigation was carried out to estimate the genetic variability, heritability and genetic advance in the garlic. The phenotypic coefficient of variation (PCV) was higher than the genotypic coefficient of variation (GCV) in all the characters. The highest GCVassociated with high heritability of with good genetic advance, was observed for weight of 10 uniform cloves followed dry weight of bulb. The lowest variability associated with low heritability and low genetic advance as percent of mean was observed for number of leaves per plant. Simultaneously, fresh weight of bulb, weight of 10 uniform cloves, dry weight of bulb and volume of bulb observed with high heritability coupled with moderate genetic advance. These traits were also governed by preponderance of additive gene effects and selection for these characters also rewarding to improve bulb yield. High heritability accompanied with low genetic advance observed for circumference of bulb, sulphur content (%), dry weight of leaves and fresh weight of leaves. It is indicative of non-additive gene action. The moderate to high heritability is being exhibited due to favourable influence of environment rather than genotype and selection for such traits may not be rewarding. Low heritability coupled with low genetic advance was found for number of leaves per plant, neck thickness, total soluble solids (TSS) and vitamin C were highly influenced by environmental effects and selection would be ineffective. High heritability in association with high genetic advance observed for plant height, number of cloves per bulb, bulb weight, and moderate heritability coupled with highest genetic advance observed for bulb yield. It indicates that most likely the heritable is due to the preponderance of additive gene effects and the potential of selection for these characters to improve bulb yield.